2001
DOI: 10.1152/ajpendo.2001.281.3.e516
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of age-related declines in glucagon-mediated signal transduction in rat liver by exercise training

Abstract: This study investigated alterations in glucagon receptor-mediated signal transduction in rat livers from 7- to 25-mo-old animals and examined the effects of exercise training on ameliorating these changes. Sixty-six young (4 mo), middle-aged (12 mo), and old (22 mo) male Fischer 344 rats were divided into sedentary and trained (treadmill running) groups. Isolated hepatic membranes were combined with [(125)I-Tyr(10)]monoiodoglucagon and nine concentrations of glucagon to determine maximal binding capacity (B(ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
3
18
1
3
Order By: Relevance
“…The catecholamine challenge in aged individuals shows deteriorated response (Morgan et al, 1983;Mabry et al, 1995;Podolin et al, 1996;Marker et al, 1998;Podolin et al, 2001). A deterioration of the catecholamine response with aging was suggested to be due to an Epinephrine induced PEPCK and PGC-1α expressions differ in young and old rat primary hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…The catecholamine challenge in aged individuals shows deteriorated response (Morgan et al, 1983;Mabry et al, 1995;Podolin et al, 1996;Marker et al, 1998;Podolin et al, 2001). A deterioration of the catecholamine response with aging was suggested to be due to an Epinephrine induced PEPCK and PGC-1α expressions differ in young and old rat primary hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the previous report by Charbonneau et al 29) Gsα, GlucR and ADRB 2 levels in liver were decreased by HFD diet. We speculated that HSHF-diet or aging could accelerate the desensitization and destruction of the hepatic Gsα-cAMP signal axis, resulting in decreased HGP, 13,[30][31][32][33] and these reduced hepatic Gsα-cAMP signal axis would finally strengthen IR and was able to cause hepatic steatosis. 29,33) This different tendency of hepatic Gsα-cAMP signal axis in progressing of IR also indicated that it is critical to select a suitable animal model in the research on different signaling molecules in IR.…”
Section: Camp Concentration In Livermentioning
confidence: 99%
“…Interestingly, Podolin et al reported that the reduction of Gsα protein was concurrent with a decrease of intracellular cAMP production with age, which may account for age-related declines in hepatic gluconeogenesis in older animals and humans. 13,14) Although many reports focused on the role of Gsα deficiency in glucose metabolism, less attention had been paid on the dynamic characterizatics of hepatic Gsα-cAMP signal axis in the process from IR to T2DM, which are important to understand the pathophysiological mechanism of hepatic IR and may also contribute to the prevention and treatment of diabe-tes. Thus, the changing characterizatics of hepatic Gsα-cAMP signal axis were studied in chronic high-sugar-high-fat (HSHF) diet-fed obese Wistar rats and diabetic db/db mice.…”
mentioning
confidence: 99%
“…Por outro lado, a realização crônica de exercícios físicos mostra-se como uma importante intervenção não farmacoló-gica no tratamento e prevenção de diversas disfunções (3) , reduzindo os fatores de risco associados ao envelhecimento e resultando em aumento da qualidade e expectativa de vida (4) .…”
Section: Introductionunclassified
“…A prática de atividade física diminui o número de internações, doenças cardíacas, diabetes e hipertensão (10,12,13) , previne o risco de quedas (14) , além de proporcionar bem-estar psicológico fundamental para melhor qualidade de vida (15) . Alguns estudos, por utilizarem-se de manipulações invasivas durante exercício físico, têm sido realizados em modelo animal, envolvendo a natação (9,16) e a corrida como forma de exercício, em ratos (3,17) . A determinação da intensidade de exercício em ratos permite simular condições de estresse físico observadas em humanos, visando o melhor acompanhamento das alterações sistêmicas decorrentes do exercício agudo e crônico.…”
Section: Introductionunclassified